Targeting mTORC2/HDAC3 Inhibits Stemness of Liver Cancer Cells Against Glutamine Starvation. Issue 20 (20th February 2022) - Zhang, Hui‐Lu; Chen, Ping; Yan, He‐Xin; Fu, Gong‐Bo; Luo, Fei‐Fei; Zhang, Jun; Zhao, Shi‐Min; Zhai, Bo; Yu, Jiang‐Hong; Chen, Lin; Cui, Hao‐Shu; Chen, Jian; et al.
Abstract: Cancer cells are addicted to glutamine. However, cancer cells often suffer from glutamine starvation, which largely results from the fast growth of cancer cells and the insufficient vascularization in the interior of cancer tissues. Herein, based on clinical samples, patient‐derived cells (PDCs), and cell lines, it is found that liver cancer cells display stem‐like characteristics upon glutamine shortage due to maintaining the stemness of tumor initiating cells (TICs) and even promoting transformation of non‐TICs into stem‐like cells by glutamine starvation. Increased expression of glutamine synthetase (GS) is essential for maintaining and promoting stem‐like characteristics of liver cancer cells during glutamine starvation. Mechanistically, glutamine starvation activates Rictor/mTORC2 to induce HDAC3‐mediated deacetylation and stabilization of GS. Rictor is significantly correlated with the expression of GS and stem marker OCT4 at tumor site, and closely correlates with poor prognosis of hepatocellular carcinomas. Inhibiting components of mTORC2‐HDAC3‐GS axis decrease TICs and promote xenografts regression upon glutamine‐starvation therapy. Collectively, the data provides novel insights into the role of Rictor/mTORC2‐HDAC3 in reprogramming glutamine metabolism to sustain stemness of cancer cells. Targeting Rictor/HDAC3 may enhance the efficacy of glutamine‐starvation therapy and limit the rapid growth and malignant progression of tumors. Abstract : Cancer cells are addicted to glutamine. When glutamine is deficient, mTORC1 is inhibited but mTORC2 is activated to regulate metabolic balance. Rictor/mTORC2 activates histone deacetylase HDAC3, which stabilizes glutamine synthase (GS) expression. GS promotes endogenous glutamine synthesis and maintains intracellular glutamine balance, which endows cancer cells with stem cell characteristics and promotes the malignant progression of cancer.